Herd Immunity Against Rabies Among Dogs in Ambon - Astri D T agueha D Tagueha; Setyawan Budiharta; Heru Susetyo (Jurnal Sain Veteriner, 2012)
The objectives of this study were to reveals factors associated with level of herd immunity against rabies. Four hundred and eighteen blood samples were collected from five subdistricts and 14 villages using stratified and  household  cluster  methods. The  result  in  ELISA  test  is    ≥  0,5  IU/ml,  dog  titers  sample  was  stated  as protective  to  rabies.  The result  showed  that  the  prevalence  of  protective  antibody  titers  was very  low  i.e.  3.35%. Linear regression  analysis reveals  subdistrict of    Nusaniwe, subdistrict of Baguala, dog owner education, post-vaccination  period  of  0  -  6  months, sex,  and  dogs  kept  as  a  guard  house  contribute  to  protective  level  of  antibody titers. Unweighted logistic regression revealed that subdistrict of Baguala (OR = 0.05), subdistrict of Sirimau (OR = 0.09), dog kept as a guard house (OR = 3.96), dog owner education (OR = 12.29), and post-vaccination period  of  0  -  6  months  (OR  =  27.08)  are  significantly  associated  with  dog's  immunity .  V accination  programs  need to  be  improved  by  considering  the  four  factors  that  emerged  in  these  two  regression  results.Keywords  :  rabies,  level  of  dog's  immunity ,  ELISA,  Ambon,  post-vaccination